2019
DOI: 10.1177/1120672119832833
|View full text |Cite
|
Sign up to set email alerts
|

An unexpected case of iatrogenic Escherichia coli endogenous pan-endopthalmitis after ERCP-associated biliary sepsis: A case report

Abstract: Introduction: Endogenous endopthalmitis is a diagnostically challenging ophthalmic and medical emergency. It has the ability to manifest at any age and is associated with a number of predisposing factors. The rapid progression of disease poses catastrophic risk for adverse outcomes both localised and systemic. To our knowledge, we describe the first reported iatrogenic case of endogenous Escherichia coli–induced endopthalmitis progressing to pan-endopthalmitis as a consequence of endoscopic retrograde cholangi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…In a retrospective study in one of the Danish centers carried out in the years 2000–2016, it was shown that complications after intestinal surgery were the source of EE in 6% of cases [ 14 ]. Both bacterial and fungal infections have been reported [ 48 , 49 ]. Complications in the form of EE development occur both after extensive surgeries, such as resection of the intestine or stomach, and definitely less strenuous endoscopic procedures [ 50 , 51 ].…”
Section: Primary Source Of Infectionmentioning
confidence: 99%
“…In a retrospective study in one of the Danish centers carried out in the years 2000–2016, it was shown that complications after intestinal surgery were the source of EE in 6% of cases [ 14 ]. Both bacterial and fungal infections have been reported [ 48 , 49 ]. Complications in the form of EE development occur both after extensive surgeries, such as resection of the intestine or stomach, and definitely less strenuous endoscopic procedures [ 50 , 51 ].…”
Section: Primary Source Of Infectionmentioning
confidence: 99%